Surgery following neoadjuvant chemotherapy for HER2-positive locally advanced breast cancer. Time to reconsider the standard attitude. Issue 6 (April 2015) - Debled, Marc; MacGrogan, Gaëtan; Breton-Callu, Christelle; Ferron, Stéphane; Hurtevent, Gabrielle; Fournier, Marion; Bourdarias, Lionel; Bonnefoi, Hervé; Mauriac, Louis; Tunon de Lara, Christine
Abstract Background While the addition of targeted therapy to neoadjuvant chemotherapy (NACT) dramatically increases the rate of pathological complete response in HER2-positive breast cancer, no reduction in the rate of mastectomy has been observed in randomised studies. Methods A retrospective single centre analysis of all patients treated with anti HER2-based NACT for T2–4 breast cancer, focusing on patients treated with mastectomy. Results Among 165 patients treated between June 2005 and July 2012, surgery was performed immediately post-NACT in 152 cases (92%). Breast-conserving surgery could be performed for 108 of the patients (71%), with a 4-year local relapse-free survival of 97%. A mastectomy was performed in two cases following patients' wishes and in 37 cases based on pre-NACT findings (n = 18) or post-NACT outcomes (n = 19). For 21 out of the 37 cases, a good pathological response was observed, and multidisciplinary reanalysis suggests that breast-conserving surgery outright may have been sufficient for 12 patients. Finally, a salvage mastectomy based on post-lumpectomy pathological results was decided in five cases (11%). The 4-year metastasis-free survival was 84% for all patients operated on after NACT (n = 152). Conclusions Given the good efficacy of anti HER2-based NACT, breast-conserving surgery should be standard practice for most patients. Total mastectomy on the other hand should be restricted to a few patients, mainly those with positive margins on the lumpectomy specimen.